Evaluation of the Effects of Surgical Varicocelectomy on the Seminal Fluid Parameters in Patients with Clinical and Subclinical Varicocele - Hammadi, Ibrahim J.; Saeed, Ghassan Th.; Abed Tawney, Read How. (Journal of the Faculty of Medicine Baghdad, 2015)
Backgound: Varicoceles defined as abnormally dilated testicular veins (pampiniform plexus) of in the scrotum and it is found in approximately 15% of the general population and associated with adverse effects on the seminal fluid and fertility. According to size of that blood vessels; the varicocele is divided into clinical that are discovered in physical examination and subclinical that are only discovered by Doppler examination. It is well known that clinical varicocele affect the seminal fluid and always treated surgically as a part of treatment of infertility or because of pain or cosmetic purpose but the controversy is about the cases of subclinical varicocele and the indication of surgery and its outcome. Objective: To assess the effects of varicocelectomy on the seminal fluid parameters of patients with clinical and subclinical varicoceles. Patients and method: 80 infertile patients with varicocele included in this study 50 had clinical and 30 had subclinical diagnosed by Doppler study. Two seminal analyses were done from the patients, one before and the other 3 to 6 months after varicocelectomy. Results: a significant improvement in the sperms count was found after the operation in both clinical and subclinical varicocele but the sperm motility percentage seems to be not affected in patients with subclinical varicocele unlike the clinical cases that showed a significant improvement after varicocelectomy. There was a non-significant decrease in the percentage of sperms with abnormal morphology in both cases. Conclusion: varicocelectomy is indicated and had good outcome on the seminal fluid parameters in cases of clinical varicocele while in cases of subclinical varicocele it should be recommended only in patients with low sperm count and assisted reproductive technique must be suggested in cases of poor motility or high percentage of abnormal sperms.